Investigating the new environmental attitude of native communities towards forest ecosystem services (Case study: Shiadeh and Diva forests) - Hamid Hajizadeh; Asghar Fallah; sare hoseini (علوم محیطی)
Introduction: The forest ecosystem, as a valuable natural resource, provides various functions and services for human beings, the maintenance of which should be the main goal of human activities. Therefore, nowadays, the study and analysis of the attitudes and behaviors of native communities to conserve forest ecosystems have become very important due to their environmental problems and challenges. Therefore, the purpose of the study is to investigate and analyze the attitude and environmental behavior of native communities on the margins of Shiadeh and Diva forests of Babol city in Mazandaran Province.Material and methods: This research is an applied research in terms of nature and the method is part of descriptive analytical research based on a survey. In this study, documentary and field methods were used to collect information. The statistical population of the study included 150 native households in the villages along the Shiadeh and Diva forests who benefited from the services of the forest ecosystem of the region. The instrument of the study was a questionnaire whose validity was confirmed by several forestry experts and its items' reliability was achieved using Cronbach's alpha test (0.87%). In the study, a single sample t-test was used to analyze data. Socio-economic variables in this study included eight variables: age, marriage, gender, occupation, household size, education, cost and income.Results and discussion:  The results of a survey of respondents' interest in the biosphere value attitude towards forest ecosystem services showed that 80.67% of the respondents had a positive view of environmental issues and 79.20% of the subjects had an altruistic view of environmental issues and 24.84% of the respondents had a selfish view of environmental issues. Also, 82.62% of native communities were willing to conserve the services of the forest ecosystem in the region. The results of data analysis showed that among the items of biosphere value attitude, altruistic, selfish and conservative, "Forests and rangeland level of the country is decreasing", "My family cares about the environment, especially the forests", "I do not have enough financial potential to pay for the conservation of the Shiadeh and Diva forests" and "To conserve the environment, I warn others and abide by forest conservation laws" items took the first rank, respectively. Also, the results of the one-sample t-test for the environmentalist attitude of native communities showed that respondents with conservative and selfish attitudes had the highest and lowest average behaviors, respectively.Conclusion: According to the results, the conservation value attitude in the research area has a higher average than other value attitudes. This indicates that native communities the environment and surrounding resources belong to themselves and strive to conserve.